2020
DOI: 10.1088/1361-6528/abc5f4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 arrays on surface enhanced Raman scattering (SERS) performance for Ag/TiO2 substrates

Abstract: Ag/TiO2 nanostructure arrays were constructed on fluorine-doped tin oxide (FTO) via a controllable hydrothermal route and a magnetron sputtering method with a variety of TiO2 arrays decorated by Ag nanoparticles. Effects of different TiO2 arrays on the microstructure, composition, and optical properties of the samples were revealed. As surface enhanced Raman scattering (SERS) active substrates, we discussed the sensitivity and reproducibility of Ag/TiO2 nanostructure arrays for Rhodamine 6G (R6G) molecule dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The light absorption properties of the as-prepared substrates were tested by the UV–vis absorption spectra. As shown in Figure A, except for the Cu foam, all of the CACNs show a strong visible light absorption in the range from 400 to 830 nm, which is attributed to the narrow band gap of both Cu 2 O and CuO, as well as the local surface plasmon resonance of Ag NPs. , Moreover, an absorption peak centered at ∼484 nm could be observed in the UV–vis spectrum of 10-CACN, as indicated within the black circle, due to the localized surface plasma resonance effect of Ag NPs. , Particularly, 10-CACN exhibits optimal absorption properties even at the near-infrared region, which could be attributed to high-density CuO/Cu 2 O nanothorns and Ag NPs. Moreover, the band gap of the CACN can be determined based on the Tauc equation ((α h ν) 2 vs h ν) (eq ), as shown in Figure B. false( α italichv false) n = A ( hv E g ) where α is the absorption coefficient that can be obtained from UV–vis spectra, h v and E g represent the photon energy and the optical band gap energy, respectively, n equals 1/2 for direct transition and 2 for indirect transition.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The light absorption properties of the as-prepared substrates were tested by the UV–vis absorption spectra. As shown in Figure A, except for the Cu foam, all of the CACNs show a strong visible light absorption in the range from 400 to 830 nm, which is attributed to the narrow band gap of both Cu 2 O and CuO, as well as the local surface plasmon resonance of Ag NPs. , Moreover, an absorption peak centered at ∼484 nm could be observed in the UV–vis spectrum of 10-CACN, as indicated within the black circle, due to the localized surface plasma resonance effect of Ag NPs. , Particularly, 10-CACN exhibits optimal absorption properties even at the near-infrared region, which could be attributed to high-density CuO/Cu 2 O nanothorns and Ag NPs. Moreover, the band gap of the CACN can be determined based on the Tauc equation ((α h ν) 2 vs h ν) (eq ), as shown in Figure B. false( α italichv false) n = A ( hv E g ) where α is the absorption coefficient that can be obtained from UV–vis spectra, h v and E g represent the photon energy and the optical band gap energy, respectively, n equals 1/2 for direct transition and 2 for indirect transition.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 8A, except for the Cu foam, all of the CACNs show a strong visible light absorption in the range from 400 to 830 nm, which is attributed to the narrow band gap of both Cu 2 O and CuO, as well as the local surface plasmon resonance of Ag NPs. 32,55 Moreover, an absorption peak centered at ∼484 nm could be observed in the UV−vis spectrum of 10-CACN, as indicated within the black circle, due to the localized surface plasma resonance effect of Ag NPs. 69,70 Particularly, 10-CACN exhibits optimal absorption properties even at the near-infrared region, which could be attributed to high-density CuO/Cu 2 O nanothorns and Ag NPs.…”
Section: Photocatalysis and Recycling Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…26,27 It is evident that the morphology, size, density of Au nanoparticles, and the hybrid pattern with semiconductors have a great influence on the hotspot region and SERS activity of the composite substrate. 28 In view of the shadow effect and high curvatures of TiO 2 nanotubes in the array, the coating of a uniform Au thin film is still challenging. Besides, the Au nanoparticles formed by dewetting of the Au thin film cannot be distributed closely enough to form a large number of hot spots throughout the TiO 2 nanotube array.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many reports about the sensitive detection with metal/semiconductor composite substrates, the research on regulation and controlling of semiconductors in SERS substrates is still far behind that of metals. Fortunately, in recent years, researchers have found that semiconductors also can be modulated in some parameters (size [23][24][25][26][27], thickness [28][29][30][31][32] and morphology [27,33]), and hence to promote their CT resonance enhancement and further optimize their SERS activities [26,34], just like the regulation of noble metals [35,36]. For example, Lombardi et al [23] optimized the size of ZnSe nanoparticles and obtained an enhancement factor of 2 × 10 6 .…”
Section: Introductionmentioning
confidence: 99%